Government Policy and Agribusiness Development in Indonesia - Pardin Lasaksi (Westscience Press, 2024)
This study examines the relationship between government policy and agribusiness development in Indonesia through a quantitative analysis. Drawing on data collected from a sample of agribusiness enterprises, the study investigates the impact of government policies on key performance indicators such as investment, productivity, competitiveness, and sustainability. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) is employed to analyze the data and assess the direct and indirect effects of government policy on agribusiness outcomes. The findings reveal significant positive relationships between government policy effectiveness and agribusiness performance indicators, highlighting the importance of supportive policy frameworks in fostering sectoral growth and rural development. Moreover, mediation the mechanisms through which government policies influence agribusiness outcomes and underscore the importance of contextual factors in shaping policy impacts. The study contributes to a deeper understanding of the dynamics shaping the Indonesian agribusiness landscape and provides actionable insights for policymakers, agribusiness stakeholders, and development practitioners to promote sustainable and inclusive sectoral development.